An integrated framework examining sustainable green behavior among young consumers. Issue 4 (25th April 2022) - Jahari, Siti Aqilah; Hass, Ashley; Idris, Izian Binti; Joseph, Mathew
Abstract : Purpose: Promoting sustainable behavior is an elusive task as it is not an innate and natural response of individuals. While a conducive environment that promotes sustainability arguably plays a prominent role in influencing individuals' belief structure and norms, not much has been done to examine the interplay between environmental, personal and behavioral domains in sustainable consumption. Drawing on the theoretical perspectives of the social cognitive theory (SCT) and value–beliefs–norms (VBN), this study aims to contribute to the literature by proposing an integrated framework that examines sustainable consumption. Design/methodology/approach: This study uses a partial least squares structural equation modeling model based on 313 young consumer responses from an eco-friendly institution in Malaysia. Findings: The findings from this study advance sustainable literature by establishing the multidimensionality concept of the personal domain of SCT. Interestingly, an enabling environment that promotes sustainability was found to be more influential in determining young consumers' beliefs and norms, as opposed to their competencies. This is demonstrated by the sequential mediation of attribution of responsibility and personal norms on the relationship between campus advertisements and pro-environmental behaviors. Originality/value: Previous research has investigated SCT and VBN as two separate streams of research in examining green behaviors. To the best of our knowledge, this is the first study that integrates SCT and VBN by examining the multidimensionality aspect of the personal construct to provide a more holistic perspective of examining sustainable behaviors.